Foundation. - Asimov, Isaac, 1920-1992. (London : HarperCollins, 1951)
As the Galactic Empire declines, psychohistorian Hari Seldon and his band of psychobiologists form the Foundation, designed to be the nucleus of an eventual ideal universal ruling corporation. The first volume of Asimov's famous science fiction saga.
Young Adult.
Keywords: Science fiction